Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/11890348_19
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Decision Criteria for WLAN Handover: Signal Strength and Frame Retransmission

Abstract: Abstract. In ubiquitous networks, Mobile Nodes (MNs) may often suffer from performance degradation due to the following two reasons: (1) reduction of signal strength by an MN's movement and intervening objects, and (2) radio interference with other WLANs. Therefore, quick and reliable detection of the deterioration of a wireless link condition is essential for avoiding the degradation of the communication quality during handover. In our previous works, we focused on a handover decision criterion allowing MNs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…That is, in a mobile environment, MNs need to promptly and reliably detect wireless link condition by exploiting the lower layer (below layer 2) information. Furthermore, our practical experiments in [4] proved that the number of frame retries on the MAC layer has the potential to detect the wireless link degradation during movement because packets over wireless inevitably experience frame retries before being treated as packet loss.…”
Section: Related Workmentioning
confidence: 93%
See 4 more Smart Citations
“…That is, in a mobile environment, MNs need to promptly and reliably detect wireless link condition by exploiting the lower layer (below layer 2) information. Furthermore, our practical experiments in [4] proved that the number of frame retries on the MAC layer has the potential to detect the wireless link degradation during movement because packets over wireless inevitably experience frame retries before being treated as packet loss.…”
Section: Related Workmentioning
confidence: 93%
“…It also cannot detect the degradation due to radio interference. Furthermore, in [4], we showed that the information of the MAC layer, frame retry, has a potential to serve as a significant metric. In this section, we describe two HO metrics employed in our new proposed method.…”
Section: Ho Decision Metricsmentioning
confidence: 96%
See 3 more Smart Citations